The emerging role of radical chemistry in the amination transformation of highly strained [1.1.1]propellane: Bicyclo[1.1.1]pentylamine as bioisosteres of anilines - Pang, Qiwen; Li, Yang; Xie, Xin; Tang, Jie; Liu, Qian; Peng, Cheng; Li, Xiang; Han, Bo (Frontiers in Chemistry, 2022)
Bicyclo[1.1.1]pentylamines (BPCAs), emerging as sp3-rich surrogates for aniline and its derivatives, demonstrate unique structural features and physicochemical profiles in medicinal and synthetic chemistry. In recent years, compared with conventional synthetic approaches, the rapid development of radical chemistry enables the assembly of valuable bicyclo[1.1.1]pentylamines scaffold directly through the amination transformation of highly strained [1.1.1]propellane. In this review, we concisely summarize the emerging role of radical chemistry in the construction of BCPAs motif, highlighting two different and powerful radical-involved strategies including C-centered and N-centered radical pathways under appropriate conditions. The future direction concerning BCPAs is also discussed at the end of this review, which aims to provide some inspiration for the research of this promising project.